PENGUATAN KINERJA PEGAWAI MELALUI PELATIHAN DAN TINGKAT PENDIDIKAN: PERAN STRATEGIS CAREER PATH PADA DINAS PENDIDIKAN KABUPATEN GOWA - Risnawati Latif; Iwan Perwira; Hernita Hernita (Journal Economic Management and Business, 2026)
This study examines the effect of training and education level on employee performance through career path at the Department of Education in Gowa Regency. A quantitative approach was employed using a survey method involving 86 respondents selected through saturated sampling. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicate that training and education level significantly influence employee performance both directly and indirectly. Furthermore, training and education level significantly affect career path, which in turn positively impacts employee performance. A career path also plays a mediating role in strengthening the relationship between training, education level, and performance. These findings confirm that human resource development strategies should not only focus on improving competencies through training and education but also emphasise structured career development systems. This study contributes to the development of human resource management theory and provides practical implications for improving employee performance in public sector organisations.